The ESA-NASA 'CHOICE' Study: Winterover at Concordia Station, Interior Antarctica, as an Analog for Spaceflight-Associated Immune Dysregu1ation - Morrels, M.; Quintens, Roel; Baatout, D. S.; Rybka, A.; Pierson, D. L.; Kaufmann, I.; Chouker, A.; Thieme, U.; Crucian, Brian E; Quiriarte, H.; Mehta, S. K.; Feuerecker, M.; et al. (2011)
For ground-based space physiological research, the choice of analog must carefully match the system of interest. Antarctica winter-over at the European Concordia Station is potentially a ground-analog for spaceflight-associated immune dysregulation (SAID). Concordia missions consist of prolonged durations in an extreme/dangerous environment, station-based habitation, isolation, disrupted circadian rhythms and international crews. The ESA-NASA CHOICE study assess innate and adaptive immunity, viral reactivataion and stress factors during Concordia winter-over deployment. To date, not all samples have been analyzed. Here, only data will be preliminary presented for those parameters where sample/data analysis is completed (i.e., Leukocyte subsets, T cell function, and intracellular/secreted cytokine profiles.)